Enhancing Classroom Engagement: Investigating Student Motivation towards Learning Physics - Zeidan, Mohammad; Young, David (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: The aim of this study is to identify effective intervention activities in the physics classroom that enhance student engagement and sustain attention toward learning physics by evaluating the impact of diverse strategies on student motivation.Methodology: The study used Vevox (an engagement platform), group work, physics simulations, and educational videos. Data were collected through pre- and post-intervention surveys, student rankings, and performance evaluations, and analyzed using statistical software for quantitative insights.Main Findings: Group work and physics simulations were found to be the most effective strategies for boosting student engagement and motivation. Students reported increased interest, enjoyment, and improved focus during physics lessons as a result of the interventions.Novelty/Originality of this study: This study offers a novel approach by integrating diverse, data-driven intervention strategies to improve student motivation in physics classrooms, providing actionable insights for educators to create more engaging and effective learning environments.